2020
DOI: 10.28991/cej-2020-03091587
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strength of Reinforced Concrete Columns Retrofitted by Glass Fiber Reinforced Polyurea

Abstract: Aged structures and structures constructed based on outdated non-seismic design codes should be retrofitted to enhance their strength, ductility, and durability. This study evaluates the structural performance of reinforced concrete (RC) columns enhanced via polyurea or glass fiber reinforced polyurea (GFRPU) strengthening. Four RC column specimens, including a reference specimen (an unstrengthened column), were tested to evaluate the parameters of the strengthening materials and the strengthened area. The tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Using Kaiser's criteria (eigenvalue > 1) and scree plot analysis, the number of variables to extract was calculated. The first EFA performed on 21 variables [ 17 , 62 ]. Following an examination of the factor loadings and item-total correlations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Kaiser's criteria (eigenvalue > 1) and scree plot analysis, the number of variables to extract was calculated. The first EFA performed on 21 variables [ 17 , 62 ]. Following an examination of the factor loadings and item-total correlations.…”
Section: Methodsmentioning
confidence: 99%
“… [ 5 , 60 ] F8 Polyurea coatings are fire-resistant, offering additional protection in a fire. [ 61 , 62 ] F9 Polyurea coatings are resistant to ultraviolet radiation, making them a viable option for concrete surfaces exposed to direct sunshine and located outside. [ 17 , 53 ] F10 Polyurea is a highly durable polymer resilient to impact, abrasion, and chemicals.…”
Section: Success Identificationmentioning
confidence: 99%
“…where 𝐹 𝑚 denotes the shear strength of the UMW and takes the minimum value of the shear strength calculated by the four failure modes of rocking, toe crushing, sliding, and diagonal tension failure specified in the Korean code [27]. 𝐹 𝐺 represents the shear strength carried by the GFRPU and is derived using the experimental results.…”
Section: (1) Modification Of Triantafillou Modelmentioning
confidence: 99%
“…Wu et al [19] investigated the reinforcing effect based on the coating thickness and compared the reinforcement effect for nonreinforced and polyurea-reinforced clay brick walls against blast loads. The reinforcement effect on concrete beams and columns reinforced by glass fiber-reinforced polyurea (GFRPU) mixed with milled glass fiber to improve the tensile strength of polyurea [20][21][22][23] was investigated. The authors reported that GFRPU was effective in enhancing the strength and ductility of structural members.…”
Section: Introductionmentioning
confidence: 99%